Influential factors in the management of pulmonary tuberculosis therapy by nurses in health centers - Djoar, Raditya Kurniawan; Anggarani, Anastasia Putu Martha (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2019)
Tuberculosis (TB) often attacks individuals who live in urban areas and have low socioeconomic levels in tropical countries such as Indonesia. Prevention efforts have been carried out by providing BCG immunization to toddlers and campaigns regarding clean and healthy living. with this effort, Indonesia has not been free from this disease. The purpose of this research was to identify factors that influence the role of nurses in the management of pulmonary TB therapy. This research is a cross sectional research and the statistical test used is Pearson correlation followed by multiple linear tests with a significance level = 0.05. Statistical test results show that there is a relationship between daily tasks and guidance of senior nurses or leaders with the role of nurses in the management of TB therapy (alpha 0,001) and multiple linear statistical tests indicate there is an influence of senior nurse or leader guidance on the implementation of the nurse's role in managing TB therapy. When seen from the results of the F value obtained simultaneously there is an influence between daily tasks and guidance of senior nurses or leaders of 55.3 percent on the implementation of the nurse's role in the management of TB therapy. Based on the results of the research, it can be used by the health center in particular to succeed in the management of TB therapy, can do a combination in the assignment of nurses where they can be assigned to the pulmonary TB service by getting guidance from senior nurses or unit leaders.Abstrak: Tuberculosis (TB) sering menyerang individu yang tinggal diwilayah perkotaan dan memiliki tingkat sosial ekonomi rendah di negara beriklim tropis seperti Indonesia. Upaya pencegahan telah dilakukan dengan memberikan imunisasi BCG pada balita dan kampanye mengenai hidup bersih dan sehat. dengan adanya usaha tersebut, Indonesia belum terbebas dari penyakit ini. Tujuan penelitian ini adalah untuk mengidentifikasi faktor yang mempengaruhi peran perawat dalam penatalaksanaan terapi TB paru. penelitian ini merupakan penelitian cross sectional dan Uji statistik yang digunakan adalah pearson korelasi dilanjutkan dengan uji linier berganda dengan tingkat signifikansi 0,05. Hasil uji statistik menunjukkan bahwa ada hubungan antara tugas harian dan bimbingan perawat senior atau pimpinan dengan peran perawat dalam penatalaksanaan terapi TB (alpha 0.001) dan uji statistik linier berganda menunjukkan ada pengaruh dari bimbingan perawat senior atau pimpinan terhadap pelaksanaan peran perawat dalam penatalaksanaan terapi TB. Apabila dilihat dari hasil nilai F didapatkan secara simultan ada pengaruh antara tugas harian dan bimbingan perawat senior atau pimpinan sebesar 55.3 persen terhadap pelaksanaan peran perawat dalam penatalaksanaan terapi TB. Berdasarkan hasil penelitian, dapat digunakan oleh pihak puskesmas khususnya untuk mensukseskan penatalaksanaan terapi TB, dapat melakukan kombinasi dalam penugasan perawat dimana mereka dapat ditugaskan di pelayanan TB paru dengan mendapatkan bimbingan dari perawat senior atau pimpinan unit.